Gender-related differences in the morphometry of the corpus callosum: MRI study - Garima Sehgal; Anupam Kumar; Navneet Kumar; Nikhil Aggarwal (Asian Journal of Medical Sciences, 2023)
Background: The size and shape of the adult corpus callosum (CC) may vary with gender. There is, however, less literature available on data involving the morphometry of CC among the Indian population.